2014
DOI: 10.3177/jnsv.60.380
|View full text |Cite
|
Sign up to set email alerts
|

α-Tocopherol Status and Altered Expression of α-Tocopherol-Related Proteins in Streptozotocin-Induced Type 1 Diabetes in Rat Models

Abstract: Vitamin E is a fat-soluble antioxidant that comprises 4 tocopherols (a-, b-, g-, and d-) and 4 tocotrienols (a-, b-, g-, and d-). Of all these vitamin E subtypes, a-tocopherol is the most well-known for its antioxidant activity (1). Lipid-soluble vitamin E has a critical role as an antioxidant protecting the lipids of the plasma membranes and lipoproteins from peroxidation. Dietary vitamin E, including tocopherols and tocotrienols, which are components of bile salt micelles, is absorbed in the intestine. Vita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In kidney tissue, the level of tocopherol is increased in all groups compared to the control group (Table 3 and 4). Takitani et al [36], and Miyazaki et al [37], reported that Alpha-tocopherol levels were elevated in liver tissue. Cholesterol is a biomolecule that is the precursor of steroid hormones and bile acids but also involved in the structure of plasma membranes and myelin.…”
Section: Resultsmentioning
confidence: 98%
“…In kidney tissue, the level of tocopherol is increased in all groups compared to the control group (Table 3 and 4). Takitani et al [36], and Miyazaki et al [37], reported that Alpha-tocopherol levels were elevated in liver tissue. Cholesterol is a biomolecule that is the precursor of steroid hormones and bile acids but also involved in the structure of plasma membranes and myelin.…”
Section: Resultsmentioning
confidence: 98%
“…Squalene is a triterpene belonging to the terpenoid family and has antioxidative, hypotriglyceridemic, and hypoglycemic effect [ 58 ]. Tocopherol which has excellent antioxidant capacity plays an important role as an antioxidant in many diseases, including diabetes and cardiovascular diseases [ 59 ]. Total phenolics and flavonoids are the most used natural antioxidant substances in TCM and show beneficial effects on the development of diabetes and cardiovascular diseases [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The α-Toc levels in the body may be influenced by changes in the mRNA expression and enzyme activity of CYP4F2. In fact, the reduced expression of hepatic TTPA, AFM and CYP4F2 genes probably leads to decreased plasma α-Toc levels and elevated α-Toc levels in the liver of streptozotocin-induced type 1 diabetes rat models [124]. Sterol regulatory elementbinding proteins can transactivate CYP4F2 transcription in hepatocytes [125], and decrease SREBP-1 proteins expression, resulting in reduced expression of CYP4F2, which slows the breakdown of α-Toc in experimental non-alcoholic fatty liver disease model mice [126].…”
Section: Atp-binding Cassette Transporter A1mentioning
confidence: 99%